Interval-Valued q-Rung Orthopair Fuzzy Choquet Integral Operators and Their Application in Group Decision-Making. (22nd August 2022) - Wan, Benting; Huang, Juelin; Chen, Xi; Cheng, Youyu; Wang, Jing
Abstract : In this paper, we develop a multiattribute group decision-making (MAGDM) method to solve problems with interactive attributes under interval-valued q -rung orthopair fuzzy set (IVq-ROFS) environment. Firstly, the interval-valued q -rung orthopair fuzzy Choquet integral average (IVq-ROFCA) operator is proposed to aggregate interval-valued q-rung orthopair fuzzy information. Then, we investigate the interval-valued q -rung orthopair fuzzy Choquet integral geometric (IVq-ROFCG) operator and offer several related properties. More importantly, for handling problems with interdependence between attributes for IVq-ROFS, a MAGDM method is developed based on the IVq-ROFCA operator. Finally, an example of the warning management system for hypertension is given to illustrate the proposed method, and parameter analysis and comparison analysis further verify the feasibility and validity of the proposed method.